Distribution of S. mutans and S. sorbinus in Caries Active and Caries Free Children by PCR Approach - Harleen Soni; Manasi Vasavada (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
Background: Streptococcus mutans (S. mutans) and Streptococcus sorbinus (S. sorbinus) have been considered to be the most important micro-organisms associated with dental caries. Therefore, purpose of this study is to detect and correlate the presence of S. mutans and S. sobrinus in the dental plaque of caries free and caries active children, by using Polymerase chain reaction (PCR) method. Materials and Methods: Twenty patients aged between ages 4-8 years were included in the study. The subjects were divided in two groups: Group A consisting of ten children with early childhood caries and Group B consisting of ten caries-free children. Dental examinations were performed using a plane dental mirror and explorer. Plaque sample was collected from the cervical margin of the teeth by using explorer. PCR testing was performed for S. mutans and S. sorbinus. The data was analyzed by using SPSS software. The caries score data was analyzed among groups by applying Fischer's exact test. The P value <0.05 was considered as significant. Results: S. mutans was present in all patients, whether they were caries active or caries free. There was no statistically significant difference in the presence of S. sorbinus in caries active patients as compared to caries free patients. It was also noticed that S. sorbinus was found more in male patients as compared to females, the difference being statistically non-significant. Conclusion: Children harbouring both S. mutans and S. sorbinus had a higher incidence of dental caries as compared to the presence of either organism alone.